Cognitive Absorption and E-learning Readiness in Learning Digitization among Preparatory Stage in Qatar (Journal Of Educational and Psychological Researches, 2023)
AbstractThe study aims to examine the relationships between cognitive absorption and E-Learning readiness in the preparatory stage. The study sample consisted of (190) students who were chosen randomly. The Researcher has developed the cognitive absorption and E-Learning readiness scales. A correlational descriptive approach was adopted. The research revealed that there is a positive statistical relationship between cognitive absorption and eLearning readiness.